Two new Thripidae (Thysanoptera) records from India with first description of Astrothrips aureolus males - Dey, Soumi; Pal, Shash; Datta, Anindita; Mandal, Sandip; Kumari, Shruti; Kumar, Vikas; Tyagi, Kaomud (Zootaxa, 2026)
Two Thysanoptera taxa are reported for the first time from India, Astrothrips aureolus Stannard & Mitri (Panchaetothripinae) and Chaetanaphothrips leucaenae Nonaka & Okajima (Thripinae). The male of Astrothrips aureolus is described based on four males collected with 12 females. Species diagnoses, illustrations and distribution details are provided.